Mechanistic Insight into the Oxidation of Organic Phenylselenides by H2O2. Issue 10 (20th January 2017) - Ribaudo, Giovanni; Bellanda, Massimo; Menegazzo, Ileana; Wolters, Lando P.; Bortoli, Marco; Ferrer‐Sueta, Gerardo; Zagotto, Giuseppe; Orian, Laura
Abstract: The oxidation of organic phenylselenides by H2 O2 is investigated in model compounds, namely, n ‐butyl phenyl selenide (PhSe( n Bu)), bis(phenylselanyl)methane (PhSeMeSePh), diphenyl diselenide (PhSeSePh), and 1, 2‐bis(phenylselanyl)ethane (PhSeEtSePh). Through a combined experimental ( 1 H and 77 Se NMR) and computational approach, we characterize the direct oxidation of monoselenide to selenoxide, the stepwise double oxidation of PhSeMeSePh that leads to different diastereomeric diselenoxides, the complete oxidation of the diphenyldiselenide that leads to selenium–selenium bond cleavage, and the subsequent formation of the phenylseleninic product. The oxidation of PhSeEtSePh also results in the formation of phenylseleninic acid along with 1‐(vinylseleninyl)benzene, which is derived from a side elimination reaction. The evidence of a direct mechanism, in addition to an autocatalytic mechanism that emerges from kinetic studies, is discussed. By considering our observations of diselenides with chalcogen atoms that are separated by alkyl spacers of different length, a rationale for the advantage of diselenide versus monoselenide catalysts is presented. Abstract : O2 on time : The oxidation of organic phenylselenides by H2 O2 provides fast and efficient in situ oxidants. A combined NMR and computational investigation is presented on four model compounds, that is the alkyl aryl selenide PhSe(nBu), the bis(phenylselanyl)alkanes PhSeMeSePh and PhSeEtSePh, and the diaryl diselenide PhSeSePh. On mechanistic and energy basis, suggestions for the choice of the most suitable organoselenium catalyst are discussed.